Acquisition by a Campylobacter-like strain of aphA-1, a kanamycin resistance determinant from members of the family Enterobacteriaceae. - Ouellette, M (1987)
A Campylobacter-like organism, BM2196, resistant to kanamycin and streptomycin-spectinomycin was isolated from the feces of a patient with acute enteritis. The kanamycin and streptomycin-spectinomycin resistances were not transferable to Camplylobacter sp. or to Escherichia coli, and no plasmid DNA was detected in this strain. The resistance genes were therefore tentatively assigned to a chromosomal locality. Analysis by the phosphocellulose paper-binding assay of extracts from BM2196 indicated that resistance to kanamycin and structurally related antibiotics was due to the synthesis of 3'-aminoglycoside phosphotransferase type I [APH(3')-I], an enzyme specific for gram-negative bacteria, and that resistance to streptomycin-spectinomycin was secondary to the presence of a 3",9-aminoglycoside adenylyltransferase. Homology between BM2196 and an APH(3')-I probe was detected by DNA-DNA hybridization. A 2.2-kilobase BM2196 DNA fragment conferring resistance to kanamycin was cloned in E. coli and was sequenced partially. The resistance gene appeared nearly identical to that of Tn903 from E. coli and was adjacent to IS15-delta, an insertion sequence widespread in gram-negative bacteria, thus indicating that Campylobacter species can act as a recipient for genes originating in members of the family Enterobacteriaceae.